Prolactin receptor gene polymorphism and the risk of recurrent pregnancy loss: a case-control study. (17th February 2018) - Kim, Jin Ju; Choi, Young Min; Lee, Sung Ki; Yang, Kwang Moon; Paik, Eun Chan; Jeong, Hyeon Jeong; Jun, Jong Kwan; Han, Ae Ra; Hwang, Kyu Ri; Hong, Min A
Abstract: Since the first study was published reporting the candidate association between the prolactin receptor gene intron C/T polymorphism (rs37389) and recurrent miscarriage, no replication study has been performed. In this study, we investigated the role of the prolactin receptor gene C/T polymorphism in 311 Korean women with recurrent pregnancy loss and 314 controls. Genotyping for prolactin receptor gene intron C/T polymorphism was performed using a TaqMan assay. The significance of difference in the genotype distribution was assessed using a chi-square test, and continuous variables were compared using a Student's t -test. The genotype distribution of the prolactin receptor gene C/T polymorphism in the recurrent pregnancy loss group did not differ from that in the control group (CC/CT/TT rates were 49.8%/41.5%/8.7% and 52.5%/37.6%/9.9% for the recurrent pregnancy loss patient and control groups, respectively, p  = .587). When the analysis was restricted to patients with three or more consecutive spontaneous miscarriages or patients without prior live birth, there were also no differences in the genotype distribution between these subgroups and controls. In conclusion, the findings of the current study suggest that the prolactin receptor gene intron C/T polymorphism is not a major determinant of the development of recurrent pregnancy loss. Impact statement: What is already known: Many studies have investigated whether there is a genetic component for the risk of recurrent pregnancy loss. Recently, one study investigated whether genetic polymorphisms involved in the regulation of the hypothalamic-pituitary-ovarian axis would be associated with recurrent miscarriage. Among 35 polymorphisms in 20 candidate genes, genotype distribution with regard to the prolactin receptor gene intron C/T polymorphism (rs37389) differed between the recurrent miscarriage and the control groups. Since this study reporting the candidate association between the prolactin receptor gene and recurrent miscarriage, no replication study has been performed. What the results of this study add: The genotype distribution of the prolactin receptor gene C/T polymorphism in the recurrent miscarriage group did not differ from that in the control group. What the implications are of these findings: Our study may be useful in that it is the first replication study since the initial report of the association of prolactin receptor gene polymorphism with recurrent miscarriage. Although no association was found, the potential role of prolactin in pregnancy loss needs to be further investigated because prolactin and its receptor have been postulated to play an important role in the maintenance of normal pregnancy.